Visual and associated affective processing of face information in schizophrenia: A selective review - Chen, Yue (Curr Psychiatry Rev, 2015)
Perception of facial features is crucial in social life. In past decades, extensive research showed that the ability to perceive facial emotion expression was compromised in schizophrenia patients. Given that face perception involves visual/cognitive and affective processing, the roles of these two processing domains in the compromised face perception in schizophrenia were studied and discussed, but not clearly defined. One particular issue was whether face-specific processing is implicated in this psychiatric disorder. Recent investigations have probed into the components of face perception processes such as visual detection, identity recognition, emotion expression discrimination and working memory conveyed from faces. Recent investigations have further assessed the associations between face processing and basic visual processing and between face processing and social cognitive processing such as Theory of Mind. In this selective review, we discuss the investigative findings relevant to the issues of cognitive and affective association and face-specific processing. We highlight the implications of multiple processing domains and face-specific processes as potential mechanisms underlying compromised face perception in schizophrenia. These findings suggest a need for a domain-specific therapeutic approach to the improvement of face perception in schizophrenia.